Fenomena Sosiologis Petani Pedesaan yang Terpinggirkan di Indonesia - Mohammad Wahed; Ririt Iriani Sri Setiawati; Kiki Asmara (OECONOMICUS Journal of Economics, 2020)
This research is a literature study regarding changes in the social phenomena of rural farmer communities in Indonesia, behavior patterns and social interaction systems, including changes in cultural norms, values ??and phenomena. The limited number of farmers is one of the reasons that underlie poverty.